2011
DOI: 10.1123/tsp.25.3.288
|View full text |Cite
|
Sign up to set email alerts
|

Do Athletes Claim Handicaps in Low Ego-Threatening Conditions? Re-Examining the Effect of Ego-Threat on Claimed Self-Handicapping

Abstract: One hundred and three athletes participated in a motor task that was ostensibly designed to detect their physical ability (high ego-threatening condition) or provide pretesting data for an upcoming study (low ego-threatening condition) and were then given the opportunity to claim handicaps that could impair their performance on this task. Extending previous findings that high self-handicappers (i.e., athletes who scored high on the self-handicapping scale) and low self-esteem athletes engage in claimed self-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(80 reference statements)
1
7
0
2
Order By: Relevance
“…Consistent with this idea, several researchers have demonstrated that trait self-esteem is related to engagement in self-handicapping strategies (Finez, Berjot, Rosnet, & Cleveland, 2011;Martin & Brawley, 2002;Prapavessis & Grove, 1998). More specifically, in the domain of sport, trait physical selfesteem -which reflects relatively stable differences in the perception of self-worth in terms of physical ability, physical self-efficacy and coordination (Fleming & Courtney, 1984) -was related to engagement in self-handicapping (Finez et al, 2011;Martin & Brawley, 2002).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Consistent with this idea, several researchers have demonstrated that trait self-esteem is related to engagement in self-handicapping strategies (Finez, Berjot, Rosnet, & Cleveland, 2011;Martin & Brawley, 2002;Prapavessis & Grove, 1998). More specifically, in the domain of sport, trait physical selfesteem -which reflects relatively stable differences in the perception of self-worth in terms of physical ability, physical self-efficacy and coordination (Fleming & Courtney, 1984) -was related to engagement in self-handicapping (Finez et al, 2011;Martin & Brawley, 2002).…”
Section: Introductionmentioning
confidence: 70%
“…More specifically, in the domain of sport, trait physical selfesteem -which reflects relatively stable differences in the perception of self-worth in terms of physical ability, physical self-efficacy and coordination (Fleming & Courtney, 1984) -was related to engagement in self-handicapping (Finez et al, 2011;Martin & Brawley, 2002). These studies demonstrated that athlete's self-ratings of physical self-esteem were especially strong predictors of self-handicapping during physical tests compared with global trait self-esteem.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…20,21,24,25,50 Prapavessis ve Grove tarafından yapılan bir çalışmada, 109 erkek golf oyuncusunun benlik saygıları ile kendini sabotaj eğilimleri incelenmiş ve düşük benlik saygısına sahip olan sporcuların kendini sabotaj eğiliminde oldukları belirlenmiştir. 25 Bir başka çalışmada, 31 basketbol oyuncusunun ego tehditi altında kaldıkları durumlarda, düşük benlik saygısına sahip olan sporcuların kendini sabotaj stratejilerine başvur-dukları sonucuna varılmıştır.…”
Section: Discussionunclassified
“…25 Bir başka çalışmada, 31 basketbol oyuncusunun ego tehditi altında kaldıkları durumlarda, düşük benlik saygısına sahip olan sporcuların kendini sabotaj stratejilerine başvur-dukları sonucuna varılmıştır. 50 Kendini sabotaj eğiliminin yordanmasına yönelik edinilen diğer bir bulgu ise sporcuların başarısızlık korkularının kendini sabotaj eğilim-lerini belirlediği ve aralarındaki ilişkinin pozitif olduğudur. Elde edilen bu bulgu doğrultusunda, başarısızlığın istenmeyen sonuçlarından kaçan ve başarısız olma hâlinden korkan sporcuların, önemli bir müsabaka ya da antrenman öncesinde kendilerini sabote etme eğiliminde oldukları söylene-bilmektedir.…”
Section: Discussionunclassified